Mechanical Implications of Creep and Partial Coupling on the World's Fastest Slipping Low‐Angle Normal Fault in Southeastern Papua New Guinea. Issue 10 (9th October 2020) - Biemiller, James; Boulton, Carolyn; Wallace, Laura; Ellis, Susan; Little, Timothy; Mizera, Marcel; Niemeijer, Andre; Lavier, Luc
Abstract: We use densely spaced campaign GPS observations and laboratory friction experiments on fault rocks from one of the world's most rapidly slipping low‐angle normal faults, the Mai'iu fault in Papua New Guinea, to investigate the nature of interseismic deformation on active low‐angle normal faults. GPS velocities reveal 8.3 ± 1.2 mm/year of horizontal extension across the Mai'iu fault, and are fit well by dislocation models with shallow fault locking (above 2 km depth), or by deeper locking (from 5–16 km depth) together with shallower creep. Laboratory friction experiments show that gouges from the shallowest portion of the fault zone are predominantly weak and velocity‐strengthening, while fault rocks deformed at greater depths are stronger and velocity‐weakening. Evaluating the geodetic and friction results together with geophysical and microstructural evidence for mixed‐mode seismic and aseismic slip at depth, we find that the Mai'iu fault is most likely strongly locked at depths of 5–16 km and creeping updip and downdip of this region. Our results suggest that the Mai'iu fault and other active low‐angle normal faults can slip in large (Mw > 7) earthquakes despite near‐surface interseismic creep on frictionally stable clay‐rich gouges. Plain Language Summary: In regions of extension, where tectonic plates pull apart, the Earth's crust breaks along fractures, or "normal faults", that allow parts of the crust to slip past each other. Many of these faults intersect the Earth's surface at a steep angle, but some anomalously low‐angle normal faults are oriented at a shallower angle to the surface. Faults can slip during infrequent fast earthquakes or through slower gradual fault creep. Because active low‐angle normal faults are rare and typically have low long‐term slip‐rates, it is not clear whether they cause large earthquakes or creep gradually. Using two approaches, this study addresses whether earthquakes occur on one of the fastest‐slipping of these types of faults, the Mai'iu fault in Papua New Guinea. One approach uses GPS measurements to track patterns of displacement of the Earth's surface near the Mai'iu fault over 3 years. Surface displacements confirm that the Mai'iu fault slips actively and are used to constrain models of fault slip at depth. The second approach uses laboratory experiments on rocks from the Mai'iu fault zone to test whether these rocks tend to slip unstably in earthquakes, or creep stably under conditions similar to those in the fault zone. Laboratory results show that rocks from the shallowest parts of the fault tend to creep stably, while deeper fault rocks tend to slip unstably. Combining laboratory, geological, and GPS results to map slip behaviors to different fault zone depths, we find that the Mai'iu fault most likely creeps near the Earth's surface but can generate larger earthquakes at greater depths. Key Points: GPS velocities reveal horizontal extension of 8.3 ± 1.2 mm/year ( 8–11 mm/year dip‐slip) on a low‐angle normal fault dipping ≤24° at the surface Shallowest gouges of this fault are frictionally weak and velocity‐strengthening; deeper fault rocks are stronger and velocity‐weakening Fault locking at 5–16 km depth with shallower and deeper interseismic creep inferred from geologic, experimental, and geodetic results